Stability analysis of a fractional model for the transmission of the cochineal - Ель Баз, О.; Айт Ічоу, М.; Лаарабі, Х.; Рачік, М.; El Baz, O.; Ait Ichou, M.; Laarabi, H.; Rachik, M. (Видавництво Львівської політехніки, 2023)
Лускокрилі — це паразитичні комахи, які уражують багато кімнатних і вуличних рослин, включаючи кактуси та сукуленти. Ці комахи є одними з частих причин захворювань кактусів: вони витривалі, розмножуються за рекордно короткий час і можуть бути згубними для цих рослин, хоча вони і вважаються стійкими. Борошнисті червці живляться соком рослин, висушуючи і знебарвлюючи іх. У цьому дослідженні пропонується та досліджується дробова модель передачі кошенілі. Спершу доводиться додатність і обмеженість розв’язків, щоб переконатися в коректності запропонованої моделі. Встановлюється локальна стійкість рівноваги без захворювання та рівноваги хронічної інфекції. Для підтвердження наших теоретичних результатів подано чисельне моделювання.

Scale insects are parasitic insects that attack many indoor and outdoor plants, including cacti and succulents. These insects are among the frequent causes of diseases in cacti: for the reason that they are tough, multiply in record time and could be destructive to these plants, although they are considered resistant. Mealybugs feed on the sap of plants, drying them out and discoloring them. In this research, we propose and investigate a fractional model for the transmission of the Cochineal. In the first place, we prove the positivity and boundedness of solutions in order to ensure the well-posedness of the proposed model. The local stability of the disease-free equilibrium and the chronic infection equilibrium is established. Numerical simulations are presented in order to validate our theoretical results.
Аналіз стійкості дробової моделі передачі кошенілі
Keywords: дробові диференціальні рівняння; кошеніль; дробова похідна Капуто; модель епідемії SIRC; локальна стійкість; чисельне моделювання; fractional differential equations; cochineal; Caputo fractional derivative; SIRC epidemic model; local stability; numerical simulations